The outward growth of the arcuate tectonic belt in the northeastern Tibetan Plateau: Insights from three-dimensional finite element numerical simulations - ZHAO Yilin; SUN Yujun; HOU Guiting; SHI Wei (Dizhi lixue xuebao)
Objective  The arcuate tectonic belt in the northeastern Tibetan Plateau is a unique boundary for the lateral growth of the Tibetan Plateau. Characterized by an arcuate geomorphology with alternating basins and mountains perpendicular to the direction of plateau expansion, it represents a unique growth mode of the Tibetan Plateau. This study aims to reproduce the formation and evolution process of the arcuate tectonic belt in the northeastern Tibetan Plateau using three-dimensional finite element visco-plastic large deformation numerical simulation. It also proposes a new structural pattern and deformation mechanism for the outward growth of the arcuate tectonic belt.  Methods  Three tests based on a large amount of geological and geophysical data were conducted to investigate how the barrier of the Yinchuan Basin and the weak lower crust control the development of faults within the arcuate tectonic belt.   Results  The results show that, as the Tibetan Plateau expanded northeastward, the shortening and thickening of the crust propagated from the plateau to the northeast. Under NE–SW compression, the deep-seated materials in the Mesozoic and Cenozoic basins (arcuate tectonic belts), which were confined by blocks, migrated northeastward. After being blocked by the rigid Ordos and Alxa blocks, these materials were squeezed into the relatively weak Yinchuan Basin to a limited extent. The obstruction by the Yinchuan Basin is an important condition for the formation and development of the faults within the shallow crust of the arcuate tectonic belt. A weak lower crust with a viscosity of 2.5×1022 Pa·s and a cohesion of 2 MPa promotes fault development within the arcuate tectonic belt, but it is not a necessary prerequisite for fault formation. This paper analyzes the distribution of the maximum shear strain rate on the surface and along three sections of the arcuate tectonic belt as well as the evolution of these characteristics over time. It is proposed that the arcuate tectonic belt generally exhibits a "ramp-thrusting" structural pattern in the deeper sections, and the deformation mechanism is characterized by deep–shallow decoupling. The deformation of the lithosphere within the arcuate tectonic belt decoupled at depths of 20 km and 40 km, forming three tectonic layers. The middle–upper crust is dominated by thrust and fold structures, regulating the horizontal shortening and vertical thickening of the crust; the weak lower crust completes the horizontal shortening and vertical thickening of the crust through ductile–plastic deformation and serves as a detachment layer for the development of arcuate structures; the lithospheric mantle, due to the regulating effect of the Moho surface, underwent limited shortening and thickening.   Conclusion  Under the control of the preexisting fault zones in the southern and northern margins and the detachment zones, the main arcuate faults developed synchronously during the period of 9.5–2.5 Ma. Then, they extended in depth and finally cut into the middle crust. [ Significance ] This study deepens the understanding of the uplift and lateral growth of the Tibetan Plateau, and provides a reference for the study of the deep–shallow processes involved in arcuate structure formation.